Evaluating the effect of synthesis, isolation, and characterisation variables on reported particle size and dispersity of drug loaded PLGA nanoparticles. Issue 17 (5th August 2021) - Garms, Bruna C.; Poli, Hamish; Baggley, Darcy; Han, Felicity Y.; Whittaker, Andrew K.; A, Anitha; Grøndahl, Lisbeth
Abstract : This work provides advice for PLGA-based nanoparticle fabrication and drug encapsulation quantification as well as the minimum required information to be reported allowing reproducibility. Abstract : Poly(lactic- co -glycolic acid) (PLGA) nanoparticles have been extensively studied as carriers of a wide variety of drugs. However, the variability in protocols and reporting in nanoscience represents a barrier to advances in new therapies. Recent literature has highlighted the challenge of reproducibility in biomedical research. In this study involving three researchers performing the experiments we therefore verified the repeatability and replicability of PLGA nanoparticles fabricated by the emulsion solvent evaporation method. Furthermore, we investigated how variables during synthesis, isolation, and characterisation of PLGA particles affect the reported particle size and drug encapsulation. Synthesis parameters including emulsification technique, type of polymer, and type of surfactant were investigated. In the isolation process, we tested the effect of washing and filtration. Dynamic light scattering (DLS) was used to determine the number weighted mean, z -average, and polydispersity index (PDI). Direct visualization of the particles was achieved by scanning and transmission electron microscopies. Changes in the source of energy input to the system using a sonic probe and homogeniser showed the most pronounced effect on particle size and PDI. This work has demonstrated that particle properties are affected by multiple variables involved in the synthesis and isolation processes. We provided advice for PLGA-based nanoparticle fabrication and drug encapsulation quantification as well as the minimum required information to be reported allowing reproducibility.